Why wait to be great? : it's either now or too late - Hawkins, Terry ([Place of publication not identifed] : [publisher not identified], 2013)
I remember telling few stories from my childhood to a new friend, and she commented that by looking at my website and the success I have had as a businesswoman, speaker and author, you would think I had led a charmed life.
There are only two times in life : now and too late -- Get out of that pit -- Pit language and professional pit people -- It's not always about you -- Genuine emotion is not the pit -- Gaining the courage to feel -- There are no failures in life - just feedback -- Happiness is a choice -- Perception -- Mind mechanics -- Fake it till you make it -- Flipman's strategy
Why wait to be great? :, Why
Includes index.
Keywords: SELF-ACTUALIZATION (PSYCHOLOGY)